Hybrid Area‐Emitting Transistors: Solution Processable and with High Aperture Ratios. (24th September 2015) - Muhieddine, Khalid; Ullah, Mujeeb; Maasoumi, Fatemeh; Burn, Paul. L.; Namdas, Ebinazar B.
Abstract : Area emission is realized in all‐solution‐processed hybrid light‐emitting transistors (HLETs). A new HLET design is presented with increased aperture ratio, and optical and electrical characteristics are shown.